Two novel mutations in the sixth transmembrane segment of the thyrotropin receptor gene causing hyperfunctioning thyroid nodules - GÖZÜ, HÜLYA (MARY ANN LIEBERT INC, 2005)
Autonomously functioning thyroid nodules (AFTNs) can present as hyperfunctioning adenomas or toxic multinodular goiters. In the last decade, a large number of activating mutations have been identified in the thyrotropin receptor (TSHR) gene in autonomously functioning thyroid nodules. Most have been situated close to, or within the sixth transmembrane segment and third intracellular loop of the TSHR where the receptor interacts with the G, protein. In this study we describe two novel mutations in the sixth transmembrane segment of the TSHR causing hyperfunctioning thyroid nodules. Genomic DNAs were isolated from four hyperfunctioning thyroid nodules, normal tissues and peripheral leukocytes of two patients with toxic multinodular goiter. After amplifying the related regions, TSHR and G,a genes were analyzed by single-strand conformation polymorphism (SSCP) analysis. The precise localization of the mutations was identified by automatic DNA sequence analysis. Functional studies were done by site-directed mutagenesis and transfection of a mutant construct into COS-7 cells. We identified two novel TSHR mutations in two hyperfunctioning thyroid nodules: Phe631Val in the first patient and Iso630Met in the second patient. Both mutant receptors display an increase in constitutive stimulation of basal cyclic adenosine monophosphate (cAMP) levels compared to the wild-type receptor. This confirms that these mutant receptors cause hyperfunctioning thyroid nodules.
Keywords: STIMULATING HORMONE-RECEPTOR; TOXIC MULTINODULAR GOITER; NEEDLE-ASPIRATION BIOPSY; TSH RECEPTOR; SOMATIC MUTATIONS; NONAUTOIMMUNE HYPERTHYROIDISM; CONSTITUTIVE ACTIVATION; GEL-ELECTROPHORESIS; ONCOGENIC MUTATIONS; GERMLINE MUTATION